Post-transcriptional and post-translational regulations of drought and heat response in plants: a spider’s web of mechanisms - Guerra, Davide; Crosatti, Cristina; Khoshro, Hamid H.; Mastrangelo, Anna M.; Mica, Erica; Mazzucotelli, Elisabetta (Frontiers in Plant Science, 2015)
Drought and heat tolerance are complex quantitative traits. Moreover, the adaptive significance of some stress-related traits is more related to plant survival than to agronomic performance. A web of regulatory mechanisms fine-tunes the expression of stress-related traits and integrates both environmental and developmental signals. Both post-transcriptional and post-translational modifications contribute substantially to this network with a pivotal regulatory function of the transcriptional changes related to cellular and plant stress response. Alternative splicing and RNA-mediated silencing control the amount of specific transcripts, while ubiquitin and SUMO modify activity, sub-cellular localization and half-life of proteins. Interactions across these modification mechanisms ensure temporally and spatially appropriate patterns of downstream-gene expression. For key molecular components of these regulatory mechanisms, natural genetic diversity exists among genotypes with different behavior in terms of stress tolerance, with effects upon the expression of adaptive morphological and/or physiological target traits.